2007
DOI: 10.31729/jnma.258
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Hepatic Function and Splenomegaly on the Newly Diagnosed Acute Leukemia Patients

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Unlike patient blood volume, however, the physiologic underpinning of this association is not known, but it is plausible that this finding also has a biologic basis. While information regarding spleen size or function was not directly captured in our study, splenomegaly occurs frequently in patients with acute myeloid leukemia (60% of our study population) and in those with leukemia evolved from myelodysplastic syndrome (another significant portion of our study population) and may correlate with disease severity . Previous studies have further demonstrated that patients with enlarged spleens also have reduced responses to transfusion .…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Unlike patient blood volume, however, the physiologic underpinning of this association is not known, but it is plausible that this finding also has a biologic basis. While information regarding spleen size or function was not directly captured in our study, splenomegaly occurs frequently in patients with acute myeloid leukemia (60% of our study population) and in those with leukemia evolved from myelodysplastic syndrome (another significant portion of our study population) and may correlate with disease severity . Previous studies have further demonstrated that patients with enlarged spleens also have reduced responses to transfusion .…”
Section: Discussionmentioning
confidence: 82%
“…While information regarding spleen size or function was not directly captured in our study, splenomegaly occurs frequently in patients with acute myeloid leukemia (60% of our study population) and in those with leukemia evolved from myelodysplastic syndrome (another significant portion of our study population) and may correlate with disease severity. 21,22 Previous studies have further demonstrated that patients with enlarged spleens also have reduced responses to transfusion. [23][24][25] While speculative, these observations logically suggest that patients in this cohort presenting with a lower starting pretransfusion Hgb may also have had more severe disease with potentially larger spleen sizes and had reduced responses to transfusion as a result.…”
Section: Discussionmentioning
confidence: 99%
“…Healthy volunteers (HV) and acute myelogenous leukemia (AML) were taken as control groups with no liver disease. Liver dysfunction is a rare complication of AML (43) and in one study of AML and acute lymphoblastic leukemia in Nepal (44), abnormal liver function tests (LFTs) were recorded in a subset of the patients. LFTs were within normal ranges for the 22 AML patients described in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In ALL, most commonly affected extra lymphoreticular sites are nervous system and testes. [6,11] Our patient had multiple retroperitoneal organs and liver/duodenal involvement at the onset and CNS involvement during treatment, indicating the more aggressive biologic behavior of tumor cells. Despite good therapeutic response achieved at initial phase, the prognosis was still poor.…”
Section: Discussionmentioning
confidence: 85%